Serious games vs. traditional tutorials in the pandemic: a randomised controlled trial - Tan, Su Min Joyce; Coffey, Michael J.; Blazek, Katrina; Sitaram, Neela; Dobrescu, Isabella; Motta, Alberto; Chuang, Sandra; Ooi, Chee Y. (Frontiers in Medicine, 2024)
Background and aim The COVID-19 pandemic necessitated the transition to online medical education. This study evaluated the efficacy of online case-based tutorials using a serious game tutorial [PlayMed™ (PM)], as compared to a traditional slideshow tutorial (TT). Methods We performed a prospective, mixed-methods, randomised controlled trial on undergraduate medical students during the COVID-19 pandemic, from May 2020 to January 2021. Students were block randomised into the PM or TT groups. Tutors conducted online teaching on bronchiolitis and gastroenteritis cases using PM or TT to facilitate the presentation. Educational experience was assessed using a continuous interval scale (0–100; with pre-defined categories) and free text responses. Immediate and long-term knowledge acquisition was assessed using 6 multiple-choice questions (MCQ) for each case (total of 12 MCQ). A modified intention-to-treat mixed methods and a sensitivity per-protocol analysis were performed to compare outcomes between PM and TT groups. Results In total, 80 PM and 73 TT participants attended at least one tutorial. Sixty-five (81%) PM and 52 (71%) TT participants completed at least one survey and were included for analysis. PlayMed™ students had an increased likelihood of completing the surveys, which included the MCQ [odds ratio (95% CI) of 2.4 (1.6–3.8), p < 0.00006]. Regarding the immediate reactions post bronchiolitis and gastroenteritis cases, several responses were significantly more positive in the PM group compared to the TT group; e.g. ‘The learning activity was engaging’ [medium effect size: d (95% CI) = 0.58 (0.32–0.85), p < 0.0001]. Higher proportions of participants in the PM group reported feeling safe in the gastroenteritis and bronchiolitis tutorials (96 and 89%), compared to the TT group (76 and 74%). PlayMed™ participants significantly outperformed TT participants on the bronchiolitis MCQs done immediately post tutorial, 4.1 (1.0) vs. 3.5 (1.0), respectively, p = 0.004 [medium effect size: d (95% CI) = 0.54 (0.16–0.91)]. Conclusion This study demonstrates the utility of a serious game (PlayMed™) as an online teaching tool for medical education. Students exposed to PM demonstrated superior engagement and feelings of safety. Utilisation of serious games may also facilitate knowledge acquisition, at least in the short term.